INFLUENCE OF NITROGEN, PHOSPHORUS AND POTASSIUM ON GROWTH, YIELD AND QUALITY OF OKRA CV. PRABHANI . PRABHANI KRANTI UNDER SUB KRANTI UNDER SUB KRANTI UNDER SUB - TROPICAL CONDITION OF MANIPUR - ANAL, P. S. MARIAM; MUNSI, P. S. (The Bioscan, 2018)
The okra cv. Prabhani Kranti responded well to the application of 80 kg N, 60 kg P2 O5 and 30 kg K2 O per hectare as evidenced by the increased in plant height, leaf area index, stem thickness, number of nodes and dry weight of the plant and NAR, green fruit yield (156.53, 143.84 and 138.56 q/ha), fruit weight per plant, number of fruit per plant and green fruit length. More number of days was required to achieve 50% flowering and maturity of green fruit at higher dose of nitrogen but phosphorus and potash could not significantly influence on this characters. Significant increase in crude protein content (16.20, 15.07 and 15.21%) of green fruit was associated with 80:30:30 kg NPK/ha. The application of nitrogen and potassium had a negative influence on the crude fibre content of green fruit. From the present study it can be concluded that the application of 80 kg N, 60 kg P2 O5 and 30 kg K2 O per hectare is the most suitable dose for higher yield and quality of okra under acidic soil condition of Manipur.